OAB score: A clinical model that predicts the probability of presenting overactive detrusor in the urodynamic study - Arribillaga,Leandro Cristian (2018)
ABSTRACT Purpose To create a predictive model of involuntary detrusor contraction (IDC) to improve the diagnostic accuracy of overactive detrusor (OAD), associating overactive bladder (OAB) symptoms with other clinical parameters in the female population. Materials and Methods A total of 727 women were studied retrospectively. In all of them, urodynamic study was conducted for urogynecological causes. Demographics information, personal history, symptoms, physical exam, a 3-day frequency/volume chart and urinary culture, were collected in all patients and they subsequently underwent uroflowmetry and urodynamic studies. A logistic regression model was performed in order to determine independent predictors of presence of IDC. Odd ratio (OR) estimation was used to assign a score to each one of the significant variables (p≤0.05) in the logistic regression model. We performed a ROC curve in order to determine the predictive ability of the score in relation to the presence of OAD. Results presence of OAD was evident in 210 women (29%). In the logistic regression analysis, independent predictors of OAD were urgency, urgency incontinence, nocturia, absence of SUI symptoms, diabetes mellitus, reduction of vaginal trophism and bladder capacity below 150 mL. The probability of IDC diagnosis increases as the score raises (Score 0: 4% until Score ≥10: 88%). Sensitivity was 71% and specificity 72%. The area under the curve of OAB score was 0.784 (p>0.001). Conclusions OAB score is a clinical tool that shows higher diagnostic accuracy than OAB symptoms alone to predict overactive detrusor.